Policy analysis for delivery of Contagious Bovine Pleuropneumonia control technologies in sub-Saharan Africa - Onono, J.O.; Wieland, Barbara; Suleiman, A.; Rushton, Jonathan (World Organisation for Animal Health, 2017)
This paper presents a policy analysis for the implementation of contagious bovine pleuropneumonia (CBPP) control strategies in pastoral regions of sub-Saharan Africa, where the disease is endemic. A framework for policy analysis was adapted for this review. The framework has eight principal steps: defining the context of the policy, identifying the problem to be addressed by the policy, searching for evidence of the problem, identifying policy options, projecting policy outcomes, evaluating the potential policy options, weighing their outcomes and making the policy decision. The data and information used to search for evidence of the problem, options for solving the problem, and the projected outcomes of those options were obtained from both published and grey sources of literature. The policy problem for CBPP control in sub-Saharan Africa was identified as a failure to deliver control services to farmers whose cattle are at high risk of exposure to infection. The authors suggest the adoption of signed contractual agreements between the public and private sectors to support the vaccination of susceptible herds raised in endemic regions. Implementation of this policy will increase vaccination coverage of susceptible cattle herds since current vaccination coverage is low.